2008
DOI: 10.1002/casp.993
|View full text |Cite
|
Sign up to set email alerts
|

A life of ease and immorality: Health professionals' constructions of mothering on welfare

Abstract: Mothering on welfare is often discussed as perpetuating disadvantage and discouraging individuals from meaningful social activity defined as paid employment. This is understood in the context of increasing commitment to a neo-liberalist agenda, where people are viewed as autonomous individuals in a market economy, and unequal rewards within this economy are due to individual failings. The discourse analysis presented here examines how health professionals in New Zealand construct what it means to be a mother o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…Breheny and C. Stephens illustrated here are local and reflect New Zealand understandings of ethnicity and culture and particular tensions between neoliberal and social democratic citizenship within a New Zealand welfare state (Breheny and Stephens 2008a), they also reflect international concern with pregnancy and parenthood among young women. In this paper, we examine the discourses used in the medical literature and how their use positions teenage mothers in particular ways.…”
Section: Methodsmentioning
confidence: 98%
“…Breheny and C. Stephens illustrated here are local and reflect New Zealand understandings of ethnicity and culture and particular tensions between neoliberal and social democratic citizenship within a New Zealand welfare state (Breheny and Stephens 2008a), they also reflect international concern with pregnancy and parenthood among young women. In this paper, we examine the discourses used in the medical literature and how their use positions teenage mothers in particular ways.…”
Section: Methodsmentioning
confidence: 98%
“…Bauman, ; Dixon & Levine, ; Henriques, ; Pickering, ; Salter & Adams, ) argue that experimental social psychology under‐theorises (or either ignores, is uninterested in or fails to countenance) the role played by neoliberalism as a contemporary institutional driver of prejudiced attitudes and behaviour. A good example of this is Breheny and Stephens () study of young mothers on welfare, who as a social category were found to be prejudiced against by health care professionals because they were seen as being unable to self‐govern (this study is discussed in more depth in the conclusion and implications section of this paper).…”
Section: The Commodification Of Self‐identitymentioning
confidence: 94%
“…Social psychological studies into health behaviours often use the categories ‘healthy’ and ‘psychopathological’. Healthy behaviours are typically deemed to be aligned with the goals of rational economic self‐interest, reflecting the dominant conceptualisation of self‐identity in neoliberalism (Aldridge, ; Breheny & Stephens, ; Sugarman, ; Tuffin, Morgan, Frewin, & Jardine, ). Take for example this quote from a text book on applied social psychology:
Health problems are related to unhealthy eating habits and a sense of not being able to control one's appetite, and environmental problems result in part from growing consumption levels and a tendency to pay attention only to one's immediate interests.
…”
Section: Governing Self‐regulating Consumersmentioning
confidence: 99%
See 2 more Smart Citations